PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KINERJA GURU DI SMP-IT AMANAH KOTA SUNGAI PENUH - qadarsih, Antri mariza (journal of RESIDU, 2018)
This study aims to determine the Principal Leadership Role in Efforts to Improve PerformanceTeachers In Junior-IT Amanah River City Full. Formulation of the problem in this research is how the Principal Leadership Role In Improving Teacher Working At SMP-IT Amanah River City Full. In Leadership Role Principal then it must be based on indicators Role of Leadership Principal: (1). Principal As Edukatot, (2). Principal As a manager, (3). As Principal Administrator, (4).Principal As Supervisor, (5). Principal As a Leader, (6). Principal For Innovators, (7). Principal As a motivator. From these results it is suggested: (1). Principal in order to understand the condition of the teacher well, has the ability to take decisions that are participatory, and has the ability to communicate well so intertwined harmonious cooperation between principals and teachers. (2). Principal should have a firmness in the dilakkan sanctions by the teacher if there is a violation of school rules that have been set together, such as in the case of late in attendance that do not fit the specified order. (3). Principal should be able to provide motivation to teachers so motivated to improve performance. In the form of awards either praise or reward, such as the election of an exemplary teacher. (4). Principal should have a strategy in developing innovative learning models such as movingclass,andanacceleratedprogram”. Keywords: Leadership, Principal, Performance